Aplicación de una metodología propuesta para el diagnóstico y el análisis de las causas raíz de los problemas operacionales durante la perforación de pozos en el Campo Castilla (2016)
This research aims to implement a proposed methodology for diagnosing the causes of operational problems of drilling in the Castilla field that have caused the recurrent increase in unplanned times and therefore increased costs during this operation. lt has an a general description of the selected field, followed by a statistical analysis in order to determine a representative sample of study is conducted. Subsequently, a tool for root cause analysis, which meets the objectives of the research are selected.